Bacterial blight of cassava - Lozano, J.C. (1975)
Bacterial blight of cassava is a serious problem in Central and South America and has been observed in parts of Africa. Symptoms include leaf spotting, wilting, dieback, gum exudation on young shoots, and vascular discoloration in mature stems and roots of susceptible cultivars. Dispersal by rain splashing is the most important means of dissemination within localized areas. Dissemination from one area to another occurs through infected planting material or by the use of contaminated tools. Delay in spread of the disease has been obtained by pruning infected plants. The use of resistant varieties and the production of certified bacteria-free planting material, obtained from plants propagated from shoot tip cuttings, has given satisfactory control. (AS)